2010
DOI: 10.1177/0145445509351961
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Adaptive Behavior Outcomes of Behavioral Intervention for Young Children With Intellectual Disability

Abstract: Data from Norway were analyzed to evaluate early behavioral intervention for children with intellectual disabilities. The intervention group (n = 11) received approximately 10 hours per week of behavioral intervention; the eclectic comparison group (n = 14) received treatment as usual. After 1 year, changes in intelligence and adaptive behavior scores were statistically significant in favor of the behavioral intervention group (effect sizes of 1.13 for Intelligence quotient (IQ) change and .95 for change in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
(23 reference statements)
1
22
0
Order By: Relevance
“…This includes a behaviourally based intervention approach mainly borrowed from the extensive research in this area for children with autism (Eldevik et al . ) and international work involving a skills‐based approach (Shin et al . ).…”
Section: Intervention Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…This includes a behaviourally based intervention approach mainly borrowed from the extensive research in this area for children with autism (Eldevik et al . ) and international work involving a skills‐based approach (Shin et al . ).…”
Section: Intervention Sciencementioning
confidence: 99%
“…However, some recent efforts directed at providing more structured curricula that are comprehensive in nature have been carried out. This includes a behaviourally based intervention approach mainly borrowed from the extensive research in this area for children with autism (Eldevik et al 2010) and international work involving a skills-based approach (Shin et al 2009). Collectively, although small in scale, this work suggested that children with delays can benefit from careful sequencing of learning activities and environmental structure, supporting a very early review of intervention effectiveness indicating that a well defined structure is a critical element in successful programmes (Shonkoff & Hauser-Cram 1987).…”
Section: Intervention Sciencementioning
confidence: 99%
“…All of these are supported by evidence of effectiveness, but none of which is truly specific to any one disorder. ABA is most-widely known for its effectiveness when used with children diagnosed with ASD (48), but ABA, and the associated early intensive behavioral intervention (EIBI) approach, has been found to be effective in other situations too (49). More broadly, psychosocial and family-based approaches are known to be effective in management of many childhood disorders (5052).…”
Section: Theme 2: Disease and Disability Perspectives: Their Goodnessmentioning
confidence: 99%